The Analysis of Income Tax Article 21 Tax Planning for Corporate Income Tax Efficiency - NARA IKA PRAYENDRA (JASS (Journal of Accounting for Sustainable Society), 2024)
Tax planning, especially related to Article 21 Income Tax (PPh pasal 21), when applied correctly, should lead to efficiency in relation to a company's Corporate Income Tax and also benefit employees in terms of their take-home pay. However, currently, some companies have not implemented PPh pasal 21 tax planning properly. This research is conducted with the aim of determining the impact of different calculation methods for Article 21 Income Tax, specifically Gross and Gross-Up, in relation to tax planning efforts aimed at saving Corporate Income Tax payments at PT. Kahatex. The applied method is a descriptive one. The research findings indicate that the Gross-Up calculation method for Article 21 Income Tax results in better efficiency in Corporate Income Tax payments compared to the Gross method, which has been traditionally used by PT. Kahatex. The Gross-Up policy also benefits employees in terms of their take-home pay. With the results of this research, it is hoped that company management will have a reference point for implementing proper tax planning for Article 21 Income Tax, thereby achieving efficiency for both the company and its employees.